Wacana Kemasyarakatan Dalam Karya-Karya Indie Di Malaysia = Social Discourse In Malaysia’s Indie Masterpieces - Mary Fatimah, Subet; Asyraff, Jamin (Penerbit UTM, 2019)
This research aimed to identify the social discourse presented in five Malaysia’s Indie novels entitled Aku Rindu 90’s (2012), Surat-Surat Untuk Kaherah (2013), Kunang Pesisir Morten (2013), Tuhan Jaga Dia Untukku (2017) and Budak Kelas Belakang (2018). This is a qualitative research using Georg Lukacs’ theory of realism (1963). Structural analysis is used to identify the views, visions, hopes and significant values for efforts to develop and improve the life quality of society. The objectives of this research were to identify Indie writer’s thoughts towards developing and improving the life quality of community, to analyse Indie novels which are equivalent to other serious mainstream media and to determine a new definiton for Indie masterpieces which evolving as a new literary stream in Malaysia. Research findings indicate that in the society there was a complete social discourse covering social, educational, economic, political and religious aspect. The findings also showed that Indie masterpieces conveyed serious thinking that particularly impact society on socials, educational, economic, political and religious developmet in a society. Indie masterpieces were also found to be on par with other serious mainstream media. The findings also showed that positive and fair valuation should be given towards these masterpieces. All findings have shown that Indie masterpieces are equivalent to other literary genres in Malaysia.